IMPLEMENTATION OF LEARNING RESOURCE CENTER MANAGEMENT IN IMPROVING STUDENT LEARNING OUTCOMES AT MA AL-IKHLAS SETUNGKEP - Sopian Irpansah Sopian (Journal of Scientific Studies and Multidisciplinary Research, 2024)
This study aims to determine the results of the implementation of learning resource center management at Madrasah Aliyah Al-Ikhlas Setungkep. This type of research is qualitative, focusing on the benefits of applying learning resource center management in enhancing student learning outcomes. The research object is the learning resource center at Madrasah Aliyah Al-Ikhlas Setungkep, and the subjects or data sources for informants in this study are 10 students at Madrasah Aliyah Al-Ikhlas Setungkep. Interviews with these 10 students revealed that the learning resource center has significant benefits in improving student learning outcomes. This is evidenced by the increase in student grades from before the resource center was fully established to after its completion. The implementation of learning resource center management at Madrasah Aliyah Al-Ikhlas Setungkep has a significant impact on providing understanding and improving student grades in the teaching and learning process. In this context, students not only comprehend and imagine the material presented but can also analyze it factually through demonstrations.